The Necessity for Rahn Guarantee Registration Agency - Syaifuddin Syaifuddin; Yasir Nasution; Tan Kamello (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
Rahn's introduction as a material guarantee law, the main arrangements contained in the Quran. By the Prophet gave an explanation of how the practice of rahn contained in the Quran. The practice of rahn by the ulema is not interpreted as a sunnah that is ta'abbudiy, but it classifies to the sunnah which is ta'aqquliy, therefore the practice of rahn can be done unlike the practices that existed during the Apostle. Thus, if the ulema interpret the order of levering marhūn does not have to be mastered physically, then there needs a legal instrument that guarantees the marhūn can be used as repayment of rāhin’s debt. For this reason, the instrument is marhūn, it is registered in the space provided. Thus, the rahn guarantee registration agency is needed.